Thinking with type : a critical guide for designers, editors, and students - Lupton, Ellen, ....- (New York : Princeton Architectural Press, 2024)
The bestselling Thinking with Type in a revised and expanded third edition: This is the definitive guide to using typography in visual communication. Covering the essentials of typography, this book explores everything from typefaces and type families to kerning and tracking to grids and layout principles. Ellen Lupton provides clear and focused guidance on how letters, words, and paragraphs should be aligned, spaced, ordered, and shaped. Historical and contemporary examples of graphic design show how to learn the rules and how to break them. Critical essays, eye-opening diagrams, helpful exercises, and dozens of examples and illustrations show readers how to be inventive within systems that inform and communicate.
Keywords: Typography